ANALISIS KESALAHAN SISWA KELAS X SMA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI NILAI MUTLAK - Suny Guinesya Ardiansyah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Problems presented in the form of stories become a problem in learning mathematics. Most of the students, consider the problem with the form of this story is very difficult, especially on certain materials. Absolute Value is the initial material learned by class X students. Many applications in everyday life use the concept of Absolute Value such as displacement, distance, area, and others without recognizing the negative sign on the results obtained even though they are in different directions. This research was conducted to find out the errors of class X students in solving the problems presented in the form of stories on the Absolute Value material by analyzing errors. This research uses descriptive qualitative research with case studies as the research method. The subjects used in this study were students of class X in one of the senior high schools in Bandung Regency. Research data collection was done by conducting a limited test of 10 students and interviews. Data analysis consisted of 30 answers from 3 questions which were answered by 10 selected students using the stages of analytical techniques, namely data collection, data processing, and drawing conclusions. The results obtained were 3 errors in answering the questions in the form of stories, namely errors in changing story questions to mathematical modeling which were called errors in making mathematical models, errors in concepts or using formulas, and errors in writing conclusion answers.